A clinical study on sudden sensorineural hearing loss in tertiary care setting - Kumar, Rajesh; Armo, Usha; Swarnkar, Neha; Minj, Anupam; Damle, G. K.; Gupta, Shailendra; Singh, B. R. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Background: Sudden sensorineural hearing loss (SSNHL) is defined as a hearing loss of ≥30 dB over at least three contiguous frequencies within 72 hours. Despite multiple theories, in most cases, no definitive cause is identified, making the condition idiopathic. Vascular, infectious, and autoimmune mechanisms are often implicated. Given the unpredictable nature of SSNHL and variability in recovery, understanding its etiology, symptomatology, and severity patterns is essential for clinical management. Methods: A cross-sectional observational study was conducted on 77 patients at R.S.D.K.S. GMC and MRD Memorial Hospital. Patients underwent audiological, vestibular, hematological, and imaging assessments. Severity of hearing loss and symptom associations were evaluated. Results: Most affected age group was 31–40 years (22.08%). Male predominance was evident (70.13%). The most frequent symptom was aural fullness (44.16%). Profound hearing loss was most common (37.66%). Major known causes included diabetes and hypertension (9.09% each), while 64.94% of cases remained idiopathic. Conclusion: SSNHL predominantly affects middle-aged males and often presents with profound loss. Most cases are idiopathic. Early diagnosis and intervention are critical to improving outcomes.